SHIREEN Whistleblower Reveals That The U.S. Covered Up An Israeli Murder Of An American Citizen. - Dissident, The (The Dissident, 2025)
A whistleblower has recently revealed that the U.S. government found that the IDF intentionally killed American journalist Shireen Abu Akleh, in the West Bank in 2022, and then covered it up.